Purgatory and piety in Brittany: 1480 - 1720 - Tingle, Elizabeth C. (Catholic Christendom, 1300 - 1700, 2012)
Setting the scene : the Catholic Church and religious life in early modern Brittany -- Purgatory and the Counter Reformation in France, 1480-1720 -- Strategies for eternity : perpetual foundations for intercession and their evolution over time, 1480-1720 -- The individual alone before God : motives of donors and the functions of perpetual masses -- Collective intercession and mutual assistance before eternity : parish, confraternity and indulgence -- The prayers of priests : chaplains and intercession for the dead